Hypoxia activates a latent circuit for processing gustatory information in C. elegans - Pocock, Roger (2010)
Dedicated neuronal circuits enable animals to engage in specific behavioral responses to environmental stimuli. We demonstrate here that hypoxic stress enhances gustatory sensory perception via novel circuitry in the nematode Caenorhabditis elegans. The hypoxia-inducible transcription factor HIF-1 upregulates serotonin (5-HT) expression in specific sensory neurons not normally required for chemosensation. 5-HT subsequently signals to promote hypoxia-enhanced sensory perception using a metabotropic G-protein-coupled receptor, SER-7, in an unusual peripheral neuron, the M4 motor neuron. M4 relays this information back into the central nervous system via the FMRFamide-related neuropeptide FLP-21 and its cognate receptor NPR-1. Thus, physiological detection of hypoxia results in the activation of an additional, previously unrecognized circuit for processing sensory information that is not required for sensory processing under normoxic conditions.